1973
DOI: 10.1128/aac.3.5.575
|View full text |Cite
|
Sign up to set email alerts
|

Active Insolubilized Antibiotics Based on Cellulose and Cellulose Carbonate

Abstract: The coupling of a number of antibiotics to cellulose and cellulose trans-2, 3-carbonate under a series of coupling conditions has been investigated, and it has been shown that by such couplings active insoluble derivatives of antibiotics can be produced. It was found that the antibiotics became firmly bound to cellulose itself, whereas use of cellulose carbonate extended the range of antibacterial activity retained. In the case of cellulose, it was considered that physical adsorption phenomena were operating, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 6 publications
(3 reference statements)
0
20
0
Order By: Relevance
“…Although for each of these transition metals, including titanium"', other, more complex ionic species may be present, these are considered to be of less importance in the chelating reactions. Previous work (8) has shown that cellulose itself may tenaciously bind, albeit noncovalently, antibiotics in such a way that in certain instances some of the antibiotic activity is retained. The coupling to cellulose was carried out under these (2) 8), and the cellulose-metal-antibiotic chelates (Table 1) reveals that it is advantageous to use the cellulose-metal-antibiotic chelate derivatives, since wider spectra of activities of the product-immobilized antibiotics are achieved.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Although for each of these transition metals, including titanium"', other, more complex ionic species may be present, these are considered to be of less importance in the chelating reactions. Previous work (8) has shown that cellulose itself may tenaciously bind, albeit noncovalently, antibiotics in such a way that in certain instances some of the antibiotic activity is retained. The coupling to cellulose was carried out under these (2) 8), and the cellulose-metal-antibiotic chelates (Table 1) reveals that it is advantageous to use the cellulose-metal-antibiotic chelate derivatives, since wider spectra of activities of the product-immobilized antibiotics are achieved.…”
mentioning
confidence: 99%
“…The potentials of active insolubilized derivatives of antibiotics for the production of antimicrobial surfaces and slow-release formulations in medical and industrial fields have already been discussed (8,10). Practically, preliminary work showed that streptomycin and gentamicin can be attached to specialized polymers, poly(N-acryloyl-4-and -5-amino-salicylic acids) (8).…”
mentioning
confidence: 99%
See 3 more Smart Citations